APPLICATION OF THE SMALL GROUP DISCUSSION METHOD IN THE STUDY OF THE BOOK WASHOYA AL-ABA LIL ABNA IN ISLAMIC BOARDING SCHOOLS - Latif, Didin Abdul (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to describe the application of the Small Group Discussion Method in book studies Washoya Al-Aba Lil Abna at the Daarul Muntaha Sukaraja Islamic Boarding School Lebak-Banten. This research method uses qualitative methods. This type of research uses descriptive research. This research found that the application of the Small Group Discussion method went through 3 stages, namely preparation, implementation and evaluation. This is done so that the discussion runs as it should. The initial step taken by the teacher is to prepare in advance the setup of the requirements needed for the discussion. Starting from admission to the teaching materials that will be delivered. Apart from that, the teacher also provides an introduction and motivation to the students so that the students are enthusiastic about participating in learning activities. After providing an introduction and explanation first, the teacher starts the discussion. In its application, teachers always rely on existing theory and conditions. The final step taken after the discussion is to evaluate what has been implemented. Starting from answering students' confusion or correcting students' wrong understanding and asking students several questions regarding the studies that have been discussed as a form of students' understanding and seriousness in following the Small Group Discussion method. This research concludes that the application of the Small Group Discussion method in book study Washoya Al-Aba Lil Abna at the Daarul Muntaha Sukaraja Lebak-Banten Islamic boarding school is in accordance with the theories and steps in the Small Group Discussion method. So the application of this method is said to be effective because it can be seen from the increase in student learning outcomes and student activity in discussions.